Strategi Pengembangan Produk Bank Syariah Di Indonesia - Ahmad Mukhlisin; Aan Suhendri (JES (Jurnal Ekonomi Syariah), 2018)
At present Islamic banking is growing rapidly, along with these developments various types of Islamic Bank products are also growing, where product innovation is the key to Islamic banking to be more competitive and more rapidly developed in accordance with the needs of the community. Product development strategies are one aspect of a marketing strategy. Banking product development is an effort to increase customers by introducing new banking products. The strategy of developing banking products is an effort to increase the number of customers by developing or introducing new banking products. Innovation and creativity in product creation are one of the main keys in this strategy. In general, every Islamic bank in running its business has five operational principles, namely as follows: Principles of pure savings, the principle of profit sharing, the principle of buying and selling, the principle of rent, and the principle of service (fee). Product development strategies are part of a corporate strategy. Islamic banks provide many options for the community to obtain financing that does not only depend on one type of bank with its products, if Islamic banks are able to read the potential of the region and the needs of the population is owned by Islamic banking, the development of Islamic banking products is a necessity for Islamic banks those in the region to be able to answer the needs of the community. This condition can occur can not be separated from the support of DPS who must be active and innovative and be with each bank in the area. As well as product marketing strategies must be carried out by conducting strategic alliances with mass media (radio, television and print media) and event organizers in the form of exhibitions (expo), so that these products are widely known and directly felt by the public at large. In certain expos such as people can directly register for sharia credit cards or make financing requests for the purchase of sharia products that are on display. Through this strategy Islamic banks can get a lot of success, both in increasing portfolios and marketing new products. Keywords: Product Development Strategy, Indonesia Shariah Bank